PENGARUH LEVERAGE, PROFITABILITAS DAN KEBIJAKAN DIVIDEN TERHADAP NILAI PERUSAHAAN - reyhan el aziz, dennis; Hascaryani, Tyas Danarti (Contemporary Studies in Economic, Finance and Banking, 2024)
The economic conditions in the era of globalization have rapidly evolved, leading to fierce competition among companies operating in various business sectors. Competition in the business world drives every company to continually improve its performance to survive and grow, making the company's value a crucial factor for investors in allocating their capital. With the existence of the capital market, entities with surplus funds can invest them, while companies can utilize these funds for investments without waiting for revenue from operational activities. The aim of this research is to determine the influence of leverage, profitability, and dividend policy on company value. The purposive sampling method is employed by selecting companies listed in the IDX30 index on the Indonesia Stock Exchange and consistently listed during the period of 2018-2020, which also consistently issue dividends annually. Data is analyzed using panel data regression. The research findings demonstrate that leverage and profitability significantly affect company value, whereas dividend policy does not significantly influence company value.